Power Consumption Analysis in DUDe 5G MIMO Networks - Chrysostomos-Athanasios Katsigiannis; Apostolos Gkamas; Konstantinos Tsachrelias; Christos Bouras; Vasileios Kokkinos; Philippos Pouyioutas (15th International Conference on Network of the Future (NoF 2024), October 2 – 4, 2024, Barcelona, Spain, 2024)
The advent of 5G technology has brought unprecedented advancements in wireless communication, promising higher data rates and improved user experiences. However, the implementation of Multiple-Input Multiple- Output (MIMO) techniques in 5G networks has significantly increased power consumption, posing a challenge to sustainability and operational costs. This study conducts a comparative analysis of energy efficiency in 5G MIMO networks, specifically between Downlink Uplink Coupling (DUCo) and Downlink Uplink Decoupling (DUDe) techniques. By examining the remaining power in the Base Stations (BSs) of the implemented Heterogeneous Network (HetNet), this analysis evaluates the potential of DUDe over DUCo in managing power consumption. The findings of this study aim to assist network operators, researchers, and policymakers in developing greener and more sustainable 5G infrastructures for a cleaner, energyefficient future.